THE INFLUENCE OF THE BIG FIVE PERSONALITY ON EMPLOYEE PERFORMANCE IN CLASS IIB SIBORONGBORONG PRISON - Sianturi, Letares; Pangestuti, Naniek (Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the influence of personality type on the performance of employees in the Siborongborong Class IIB Correctional Institution. This research used a quantitative research method with a total sampling technique so that the sample used was 66 respondents. The data collection method is carried out using a questionnaire, then data analysis using a normality test, a simple linear regression test and a hypothesis test. From the results of the study, it was obtained that the value of the coefficient of determination of 0.350 which means that the big five personality variable affects employee performance by 35%, while the remaining 65% can be explained by other factors. The results of the hypothesis test obtained t count> t table (5.870> 1.99773) and significance value (0.000) < a significance level of 5% which means Ho is rejected and Ha is accepted means that the big five personality type has a positive and significant influence on the performance of employees in Siborongborong Class IIB Correctional Institution